(untitled) (Revista de História Regional, 2008)
The start up of press in Brazil happened at the same time of State formation. From 1808 to 1831, the printing press got a wide space in intellectual and political circles of Courts and of provinces. Besides, it spread at the streets, being a important vehicle of public opinion. We intend to discuss in this article some aspects of the creation of printing press in the São Paulo city, still considering little investigated points: the intellectual life in the city in the beginning of the 19th century; the local elite composition that is been inserted on national political game; and the intellectual profile from José da Costa Carvalho, creater of O Farol Paulistano, the first newspaper of São Paulo city. This study is based in our reading of some copies of the newspaper above, and the analyze of library inventory owned by José da Costa Carvalho. With this procedure, we could follow the ideological thinking of publisher and his intellectual matrix.